2006
DOI: 10.4049/jimmunol.176.11.6624
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of the TLR-5 Ligand Flagellin in Mouse Models of Cancer

Abstract: Flagellin, the structural protein subunit of the bacterial flagellum, is specifically recognized by TLR-5 and has potent immunomodulatory effects. The antitumor effects of purified Salmonella typhimurium flagellin were evaluated in mice transplanted s.c. with a weakly immunogenic murine tumor or with its variant stably transfected to express the highly antigenic human HER-2 oncoprotein. Peritumoral administration of flagellin 8–10 days after tumor implantation did not affect the growth rate of the weakly immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 46 publications
5
125
0
3
Order By: Relevance
“…In fact, activation of TLR5 by commensal bacteria was shown to drive malignant progression at extramucosal locations through the promotion of inflammation, which dampened antitumor immunity by expanding immunosuppressive networks (65). In contrast, we and others have shown that TLR5 activation has tumor growth suppressive effects and stimulates antitumor immunity (19)(20)(21)(22)(23)(24)(25)(26)53). Earlier studies in our laboratory showed that entolimod displayed a growth-inhibitory effect on a TLR5-expressing mouse xenograft model of human lung adenocarcinoma A549 (23), supporting a direct effect of TLR5 stimulation on tumor growth suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, activation of TLR5 by commensal bacteria was shown to drive malignant progression at extramucosal locations through the promotion of inflammation, which dampened antitumor immunity by expanding immunosuppressive networks (65). In contrast, we and others have shown that TLR5 activation has tumor growth suppressive effects and stimulates antitumor immunity (19)(20)(21)(22)(23)(24)(25)(26)53). Earlier studies in our laboratory showed that entolimod displayed a growth-inhibitory effect on a TLR5-expressing mouse xenograft model of human lung adenocarcinoma A549 (23), supporting a direct effect of TLR5 stimulation on tumor growth suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the only known natural TLR5 agonist, flagellin, flagellin-expressing Salmonella bacteria, and a pharmacologically optimized flagellin derivative named entolimod (CBLB502) have antitumor effects in several tumor models (19)(20)(21)(22)(23), including mouse models of liver metastases (24)(25)(26). Moreover, systemic administration of TLR5 agonists is uniquely safe because of the restricted pattern of expression of TLR5 (primarily in the gut, liver, and bladder) and the nature of the cytokines induced following TLR5 stimulation.…”
mentioning
confidence: 99%
“…In contrast, flagellin was able to promote CD8 + T cell response when fused with OVA protein, SIINFEKL peptide, or viral Ags (21)(22)(23)(24)(25). In addition, flagellin has been reported to modulate antitumor immune responses (26). However, studies with tumor models have yielded conflicting results with regard to whether flagellin actually promotes or suppresses tumor growth (26)(27)(28).…”
mentioning
confidence: 89%
“…Recently published data 42 show that purified flagellin administered peritumorally 8-10 days after tumor implantation did not affect the growth rate of a poorly immunogenic tumor, whereas it significantly inhibited the growth of an antigenic human ErB-2-transfected tumor variant. Low immunogenicity of B16F0-CAR cells might explain the lack of effect observed for Ad-flagellin.…”
Section: Adenovirus-pamps For Cancer Immunotherapy C Tosch Et Almentioning
confidence: 96%